1998
DOI: 10.1111/j.1439-0264.1998.tb00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Macro‐Anatomical Investigations on the Skeletons of Porcupine (Hystrix cristata). Part III: Skeleton axiale

Abstract: The aim of this study was to investigate the axial skeleton of two porcupines (Hystrix cristata). The important features of the skull, observed in this study are as follows: The zygomatic process of frontal bone (os frontal) was found to be rudimentary, and the infraorbital foramen (for. infraorbitale) was very large. The zygomatic bone (os zygomaticum) has two processes (frontal and temporal) and the zygomatic arch (arcus zygomaticum) was composed of three bones. The dental formulae were 2 (I 1/1, C 0/0, P 1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 1 publication
3
36
1
Order By: Relevance
“…The total number of tarsal bones and digits observed in the grasscutters was fourteen and four, respectively, the latter being the same with that seen in the New Zealand white rabbit (Oryctolagus cuniculus) (Ajayi et al, 2012). This number and arrangement differed from those reported in the African giant rat (Salami, Onwuama, Maidawa, Jibril, & Ojo, 2011), laboratory rat (Rudolf & Stromberg, 1976), porcupine (Yilmaz et al, 1999), badger (Dinç, 2001) and mole rat (Ozkan, 2002;Özkan, 2007), which all have five hindlimb digits. The longer bone segments (os coxae, femur, patella, tibia and fibula) observed in the buck vis-à-vis doe grasscutters were apparently a function of body size difference between the sexes.…”
Section: P L At E 8 Pes Dorsal (L) and Plantar (R) View (Burial Prepcontrasting
confidence: 64%
See 1 more Smart Citation
“…The total number of tarsal bones and digits observed in the grasscutters was fourteen and four, respectively, the latter being the same with that seen in the New Zealand white rabbit (Oryctolagus cuniculus) (Ajayi et al, 2012). This number and arrangement differed from those reported in the African giant rat (Salami, Onwuama, Maidawa, Jibril, & Ojo, 2011), laboratory rat (Rudolf & Stromberg, 1976), porcupine (Yilmaz et al, 1999), badger (Dinç, 2001) and mole rat (Ozkan, 2002;Özkan, 2007), which all have five hindlimb digits. The longer bone segments (os coxae, femur, patella, tibia and fibula) observed in the buck vis-à-vis doe grasscutters were apparently a function of body size difference between the sexes.…”
Section: P L At E 8 Pes Dorsal (L) and Plantar (R) View (Burial Prepcontrasting
confidence: 64%
“…A-tarsals, 1, first metatarsal; 2, second metatarsal; 3, third metatarsal; 4, fourth metatarsal; 5, first phalanx; 6, second phalanx; 7, third phalanx; 8, sesamoid bone and porcupines (Yilmaz, Dýnç, & Aydin, 1999) in which there were proximal attachment and distal third fusion with the tibia.…”
Section: P L At E 8 Pes Dorsal (L) and Plantar (R) View (Burial Prepmentioning
confidence: 99%
“…It is different from what observed for the ferret skull, which showed an elongated flat skull with a shortened facial region (He et al 2002, O'Malley 2005. There was no significant difference between bones found in the white-eared opossum skull when compared with those described for other mammals, as of porcupine (Yilmaz 1998), ferret (He et al 2002), and dog (Dyce et al 2010). Voss & Jansa (2009) reported presence of the jugal bone in the marsupial Marmosa murina.…”
Section: Discussionmentioning
confidence: 71%
“…The tympanic bulla is not well developed in Didelphis albiventris, unlike well developed in porcupine (Yilmaz 1998), ferret (He et al 2002), badger, otter, marten, cat, and dog (Karan et al 2006, Dyce et al 2010. There is no difference between bone formation found in the hard palate of the white-eared opossum skull and in the dog (Dyce et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…12,15 In some diagnostic imaging modalities, if a small field of view is used, or if the tomographic nature of the imaging excludes anatomic landmarks which might be useful in lesion localization, then identification of additional anatomic features as reference points will aid interpretation. 16 For instance, in one study, the usefulness of the coeliac and cranial mesenteric arteries as landmarks for magnetic resonance imaging of the spine was investigated, but it was found that the position of these arteries was too variable to allow them to be used as reference points.…”
Section: Discussionmentioning
confidence: 99%